Retroperitoneal Schwannoma: Unusual Cause of Radiculopathy - Rajbanshi, Jagat Narayan; Suman, Sumnima; KC, Beecase; Gurung, Pritam; Khadka, Bibek; Dhakal, Sudan; Pant, Basant (Annapurna Journal of Health Sciences, 2025)
Schwannomas are relatively common tumors that originate from the peripheral nerve sheath. They account for 4% of all tumors found in the retroperitoneal space, with schwannomas making up approx-imately 3% of that total. The occurrence of retroperitoneal schwannoma presenting with lumbar radiculopathy is quite rare. Benign retroperitoneal schwannomas generally have a favorable outcome following complete surgical removal, with a low likelihood of recurrence, while those that are only par-tially removed have a recurrence rate of 5-10%. For a definitive diagnosis, histopathological examina-tion and immunohistochemical analysis are the most effective methods.